We have always lived in the castle ebook Penguin classics deluxe edition. - Jackson, Shirley (2006)
Shirley Jackson's beloved gothic tale of a peculiar girl named Merricat and her family's dark secret Taking readers deep into a labyrinth of dark neurosis, We Have Always Lived in the Castle is a deliciously unsettling novel about a perverse, isolated, and possibly murderous family and the struggle that ensues when a cousin arrives at their estate. This edition features a new introduction by Jonathan Lethem. For more than seventy years, Penguin has been the leading publisher of classic literature in the English-speaking world. With more than 1,700 titles, Penguin Classics represents a global bookshelf of the best works throughout history and across genres and disciplines. Readers trust the series to provide authoritative texts enhanced by introductions and notes by distinguished scholars and contemporary authors, as well as up-to-date translations by award-winning translators.